Lung function in retired coke oven plant workers. Issue 5 (May 1992) - Chau, N; Bertrand, J P; Guenzi, M; Mayer, L; Téculescu, D; Mur, J M; Patris, A; Moulin, J J; Pham, Q T
Abstract : Lung function was studied in 354 coke oven plant workers in the Lorraine collieries (Houillères du Bassin de Lorraine, France) who retired between 1963 and 1982 and were still alive on 1 January 1988. A spirometric examination was performed on 68.4% of them in the occupational health service. Occupational exposure to respiratory hazards throughout their career was retraced for each subject. No adverse effect of occupational exposure on ventilatory function was found. Ventilatory function was, however negatively linked with smoking and with the presence of a respiratory symptom or discrete abnormalities visible on pulmonary x ray films. The functional values were mostly slightly lower than predicted values and the most reduced index was the mean expiratory flow, FEF25-75%. The decrease in forced expiratory volume in one second (FEV1) was often parallel to that in forced vital capacity (FVC), but it was more pronounced for subjects who had worked underground, for smokers of more than 30 pack-years, and for subjects having a respiratory symptom. Pulmonary function indices were probably overestimated because of the exclusion of deceased subjects and the bias of the participants.